A Theoretical Evaluation of Possible N2 Reduction Mechanism on Mo2B2. Issue 5 (26th March 2021) - Wang, Jia; He, Chaozheng; Huo, Jinrong; Fu, Ling; Zhao, Chenxu
Abstract: 2D MBene has similar properties to MXene, and it has received widespread attention as an efficient ammonia synthesis catalyst. Herein, the catalytic effect of 2D Mo2 B2 applied to the electrochemical nitrogen reduction reaction (NRR) by the first principles calculation is studied. It is found that 2D Mo2 B2 can form different adsorption structures which have different electronic properties, and active N2 molecules effectively. These different structures have different catalytic mechanism on the NRR process. In addition, the possibility of NRR reactions on these structures is explored and it is found that when N2 adsorbed obliquely on 2D Mo2 B2, it has the lowest overpotential (0.34 V). This work provides important reference for exploring more excellent NRR catalysis in experiments and expands the application of transition metal borides in catalysis. Abstract : In this work, the catalytic effect of 2D Mo2 B2 applied to the electrochemical nitrogen reduction reaction (NRR) by density functional calculations is studied. It is found that 2D Mo2 B2 can effectively active N≡N molecules and form different adsorption structures. These structures have different electronic properties. Subsequently, the possibility of NRR reactions on these structures is explored and it is found that when N2 molecule adsorbs obliquely on 2D Mo2 B2, it has the lowest overpotential (0.34 V). This work is the first report on MBene electrocatalyst for NRR, which offers directions for exploring more excellent N2 reaction catalysis in experiments and seeks wider application of MBene in catalysis.